Isolasi dan Identifikasi Bakteri Selulolitik pada Sampah Upacara Agama di Pura Goa Lawah Klungkung - SANI, NI MADE ADHYA NIDIDHYA; ADIARTAYASA, WAYAN; WIRAWAN, I GEDE PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.2, April 2021, 2021)
Isolation and Identification of Cellulolytic Bacteria in Religious Ceremony Waste at Goa Lawah Temple Klungkung Cellulolytic bacteria are bacteria that can hydrolyze cellulose complexes into smaller oligosaccharides and finally glucose. Cellulolytic bacteria synthesize a set of enzymes that can hydrolyze cellulose called cellulase enzymes. This study aims to isolate and identify cellulolytic bacteria that have the potential to degrade cellulose by taking organic waste samples from TPS Pura Goa Lawah Klungkung. Characterization was carried out by growing selected pure isolates on CMC media and then dripping with congored 0.1% to test their cellulolytic potential. The results of bacterial isolation at 10dilution -8 obtained 28 bacterial isolates that were able to grow and utilize cellulose as a carbon source. From the isolation results obtained The 4 bacterial isolates each had different morphological characters capable of producing clear zones with a diameter of 10 mm: 5 mm respectively; 3 mm and 4 mm. The results of the isolation of bacterial colonies appeared to be round and irregular in shape, had clear and cream colors, had a convex and flat surface and all isolates had smooth edges. Type C bacterial isolates included gram-negative groups, bacterial isolates A, B and D included gram-positive groups and all bacterial isolates A, B, C and D were rod-shaped. The degradation ability based on the cellulolytic index value of bacterial isolate A was in the highest category compared to bacterial isolates B, C and D.